Pyrite zoning as a record of mineralization in the ventersdorp contact reef, Witwatersrand Basin, South Africa - Agangi, Andrea; Hofmann, A.; Wohlgemuth-Ueberwasser, C. (2013)
The Archean metasedimentary succession of the Witwatersrand basin, South Africa, hosts the largest Au deposit in the world. Gold mineralization is mostly concentrated in conglomerate horizons, or "reefs," and is tightly associated with pyrite. Trace element zoning of pyrite from the Ventersdorp Contact Reef, studied by X-ray elemental (As, Ni, Co, and Pb) maps, electron microprobe analysis, and laser ablation-inductively coupled plasma-mass spectrometry, indicates successive stages of pyrite formation, each characterized by different textures and trace element composition (As = 2.2 wt %, Ni = 1.37 wt %, Co = 1.98 wt %). Four generations have been distinguished: generation 1 is detrital and includes compact (nonporous), porous, and laminated pyrite; generations 2 to 4 are postsedimentary/authigenic. Generation 4 pyrite formed at near-peak metamorphic conditions (T = 270°-350°C, chlorite geothermometry). Porous and concentrically laminated pyrite grains (generation 1) are particularly enriched in Au (average 6.4 ppm, maximum 70 ppm), in addition to Sb, Tl, Pb, Mn, Mo, Cu, and Ag, in comparison with compact pyrite types of all generations. In these grains, Au, occurring as "invisible gold," and other trace elements might be finely dispersed with the phyllosilicates filling the pyrite pores. Trace element composition of porous and concentrically laminated pyrite is reminiscent of pyrite known to form in suboxic to anoxic environments (black shales). The presence of Au in detrital pyrite indicates an early introduction of Au in the Ventersdorp Contact Reef. Gold is also present as secondary inclusions of electrum associated with the last pyrite generation (generation 4), together with sphalerite, chalcopyrite, galena, and pyrrhotite. © 2013 Society of Economic Geologists, Inc.